INTERTEKSTUALITAS HADIS PEREMPUAN SHALAT BERJAMAAH DI MASJID - Muhammad Habib Zainul Huda (Academic Journal of Islamic Principles and Philosophy, 2022)
This paper examines how to understand hadith in a socio-cultural political context. The author takes the example of the hadith, "Women Pray together in Mosques". The method that the author uses, contextual historical analysis by using the interconnection paradigm. This paper includes a type of literature by referring to Abdul Mustaqim’s writing, "The Science of Ma’anil Hadith". The difference between this writing and the writing is, the application of the hadith studied. This writing is interesting and important to study, one of the reasons is, in Ramadan women worshipers in mosques more than in other months, of course it is Caused bythe understanding of the hadith above. Thus, the event gave rise to the Novelty of this writing, to reveal the true meaning of the hadith above. Among the conclusions of this paper : (1) The Importance of Asbabul Wurud, Stilistic, Socio-Historical Approach, Contextual-Redaction Analysis, destination, InterconnectionParadigm (Anthropology, Sociology, Psychology) in understanding hadith. (2) In considering the Socio-Cultural Context of Politics in understanding hadith, there is expected to be a compromise and dialogue between the use of hadith in the context of the past and the current context. (3) There is a hadith that seems mukhtalif about the virtues of women’s prayers in the mosque. After being analyzed, it shows that: "There are virtues and wisdoms for women who pray in mosques rather than praying at home, especially in this day and age, while still paying attention to various conditions, conditions and ethics".